THE ISSUE OF OPTIMIZATION OF THE LEGAL REGULATION OF CERTIFICATION OF GENERAL AVIATION AIRCRAFT: DOMESTIC AND INTERNATIONAL EXPERIENCE - Cherevatiuk, Vyktoriia; Zuieva, Vyktoriia (Proceedings of National Aviation University, 2017)
Purpose: to reveal directions of optimization of the legal adjusting of certification of air ships of general aviation, by realization of analysis of rules, procedure and subjects of registration of civil air ships and permissive system in Ukraine, USA, and also in the countries of the European concord. Exposure of factors that restrain development of general aviation in Ukraine and grant to suggestion in relation to the improvement of the legal adjusting of certification of air ships of general aviation. Methods: the use of approach of the systems allowed to reveal basic directions of optimization of the legal adjusting of certification of air ships of general aviation of Ukraine, being base on experience of leading countries of the world. Results: in the article attention is accented on the lacks of the legal adjusting of Ukrainian general aviation, in particular, to the legislative vagueness of concept of general aviation that limits her development in direction of realization as commercial and substantially narrows the spectrum of possibilities for her subjects, and also does this sector of aviation economically unattractive. Substantially absence of the ramified classification of air ships complicates the legal adjusting, what took into account sizes of air ship, engine, condition of take off the plane and landings, distance of flights, carrying capacity and other. The questions of optimization of the legal adjusting of certification of air ships of general aviation touch simplification of procedure of certification for ultralight , being base on experience of the USA, Canada, and also some countries of Europe. Discussion: authors offer the ways of optimization of the legal adjustment of certification of air ships of general aviation of Ukraine.